Spectrophotometric Study of Doped Pr(III) Ion in Saturated Solutions of Carbohydrates and Amiles in Non-aqueous Solvents - Balani, Daya; Maurya, Shakuntala; Joshi, G.K.; Tater, P.C.; Jain, S.L. (Asian Journal of Chemistry, 2012)
The stereo-environment of doped Pr(III) ion in saturated solutions of carbohydrates (glucose, fructose and sucrose) and amides (acetamide, urea and thiourea) in DMF as well as in DMSO has been discussed on the basis of Judd-Ofelt intensity parameteric ratio (T4/T6). Pr(III) ions doped with the various systems have been characterized on the basis of various electronic spectral parameters viz. Slater-Condon (Fk) Lande' (ζ4p) intensity of hypersensitive transition (3P2), Judd-Ofelt (Tλ) and bonding parameter (b1/2).